Efficient Learning on Imbalanced Image Set - Guldas, Shivani (International Journal of Computer Sciences and Engineering, 2025)
Handling imbalanced image sets is a challenging issue being faced by the conventional categorizer. Imbalance problem occur with real world data due to various reasons, to which the ordinary classifiers gets influenced towards major class data. In this paper, we aim to balance bi-class absolute image set by creating synthetic samples of minority class images. Tests on three image sets using five synthetic image generation methods, four image features and three evaluation measures is carried out. KNN classification is performed on all three image set which are pretty imbalanced and the results indicate that synthetic creation of minor class images progresses the performance measures